Etude de l’activité antagoniste de quelques Rhizobactéries vis-à-vis de Fusarium oxysporum f.sp. ciceris - SBAIHIA, Lyes; YAHIATENE, Sara Fatna (My University, 2019)
Fifteen strains of rhizobacteria isolated from the rhizosphere of potato plants in the region of Mostaganem are evaluated for their antagonistic activity on the growth and sporulation of two isolates (TLM and T9) of Fusarium oxysporum f.sp. ciceris, agent for fusariosis of chickpea (Cicer arietinum L.). For this two distinct (direct and indirect) confrontation methods were tested. In direct comparison, the growth radius of the TLM isolate varies between 24 and 35 mm depending on the antagonist with which it is confronted, relative to the radius of the control not confronted with the antagonist (35 mm). The growth radius of the T9 isolate varies between 26 and 36 mm for the treatment against 38 mm for the control (T9 not confronted with any antagonistic bacteria). An important zone of inhibition of the pathogen has been noted. The antagonists tested all had an effect on the sporulation of the two parasitic strains. Indeed, the sporulation of TLM varies from 8.44 × 106 spores / ml to 52.02 × 106 spores / ml depending on the bacterium to which the isolate is confronted, against 84.33 × 106 spores / ml in the case of the control (not confounded with the 'antagonist). In the case of T9, the number of spores varies from 39.77 × 106 spores / ml to 73.2 × 106 spores / ml according to the bacteria tested, against control 85.11 × 106 spores / ml for the control. In indirect comparison, the growth radius of the parasitic fungus varies between 16 and 34 mm for the TLM isolate and 24 mm at 36 mm for the T9 isolate against 38 mm for the growth radius of the TLM control and 35 mm for the control. T9. According to the bacterium to which its colony is confessed, the sporulation of TLM varies between 12x106 to 71.11x106 spores / ml, on the other hand it varies from 24x106 spores / ml to 73.59x106 spores / ml in the case of T9, relative to the T9 controls ( 89.84 × 10 6 spores / ml) and TLM (84.66 × 10 6 spores / ml).
Keywords: Fusarium oxysporum f. sp. ciceris; vascular wilt; Cicer arietinum L.; rhizobacteria; antagonistic microorganisms